Young African Norwegian women and diaspora: Negotiating identity and community through digital social networks. Issue 1 (1st March 2014) - Mainsah, Henry
This article explores the ways in which Norwegians of African descent explore their relationship with the African diaspora through the multimodal practices of digital online media. Through the stories of two young Norwegian women the article examines how community, ties and ways of belonging are envisioned at both the local and the transnational levels, and at the intersection between online and offline spaces. These stories are drawn from a larger digital ethnography of the African diaspora in Norway. The article underlines the need to locate understandings of 'diaspora' and the 'digital' within relations and positionalities in specific national contexts and spaces. The article aims to add to the existing literature on how diasporas in general and African diasporas in particular are technologically mediated.